THE IMPORTANCE OF USING INSTRUCTIONAL TECHNOLOGY IN TEACHING PROCESS - Mavlonova Zarnigor Olimjonovna (Journal of new century innovations, 2022)
This article discusses about using instructional technology as a media in teaching process in EFL classroom. Some problems faced by students in teaching and learning process especially for student English achievement. Using instructional technology can be more effective and improve students’ English if the instructors have confidence and skills in using the technology.